Roles of CsBRC1-like in leaf and lateral branch development in cucumber. (January 2021) - Shen, Junjun; Ge, Danfeng; Song, Xiaofei; Xiao, Jiajing; Liu, Xiaofeng; Che, Gen; Gu, Ran; Wang, Zhongyi; Cheng, Zhihua; Song, Weiyuan; Liu, Liu; Chen, Jiacai; et al.
Highlights: CsBRC1-like and CsBRC1 originate from one segmental duplication in cucumber. CsBRC1-like regulates leaf development during cucumber seedling period. CsBRC1-like may regulate early leaf development through affecting the expression of auxin and cytokinin related genes. CsBRC1-like directly interacts with CsBRC1 and CsTCP10a. Abstract: TEOSINTE BRANCHED1 / CYCLOIDEA / PCF ( TCP ) family genes, as plant-specific transcription factors, play vital roles in flower pattern, leaf development and plant architecture. Our recent study shows that the TCP gene BRANCHED1 ( CsBRC1 ) specifically regulates shoot branching in cucumber. Here, we found CsBRC1 had a closely related paralogous gene CsBRC1-like . The synteny analysis revealed that these two genes originated from a segmental duplication. CsBRC1-like displayed different expression patterns in cucumber compared with CsBRC1, indicating that they may have functional differentiation. Ectopic expression of CsBRC1-like in Arabidopsis brc1−1 mutant resulted in reduced rosette branches and rosette leaves, whereas silencing CsBRC1-like in cucumber only led to a deformed true leaf of seedling rather than affecting the shoot branching. RNA-seq analysis of wild-type and CsBRC1-like -RNAi plants implicated that CsBRC1-like might regulate early leaf development through affecting the transcripts of auxin and cytokinin related genes in cucumber. Moreover, CsBRC1-like directly interacts with CsTCP10a and CsBRC1 in vivo . Our results demonstrated that CsBRC1-like has a specific role in regulating leaf development, and CsBRC1-like and CsBRC1 may have overlapping roles in shoot branching.